ANALISIS TRANSFORMASI STRUKTURAL PEREKONOMIAN ACEH - Dedi Sufriadi, Abubakar Hamzah, Sofyan Syahnur. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2015)
Abstract: The main aims of this observation are 1.to figure out the transformation of structural economy in Aceh; and 2. To analyze the economical sectors which are available to be developed in Aceh. This research was analyzed using Classic Shift Share Analysis, Esteban-Marquillas Shift Share Analysis and Location Quotient (LQ). The results based on the Shift Share Analysis shows that years of 2008-2012 there have been changes in the economic structure of Aceh primary sector to tertier sector and secondary sector. where as years of 2000-2004 and years of 2004-2008 haven`t been changes in the economic structure of Aceh. The economic structural transformation during analysis years in 2008-2012 happened because the contribution from primary sector which is decreasing with the low relative growth, but at the same time the constribution of the tertier sector is increasing with the high relative growth as well as secondary sector. Agriculture sector, mining and quarrying sector and services sector are the basis sectors and can be seeded to be developed on the economy Aceh. It’s expected that the governments, especially in Aceh to pay attention and to develop the economical sectors in Aceh. This can be done by issuing policies that potential for the development of economic sectors and also formulate policies to begin to develop the leading sectors with a focus on sectors which have the advantages as well as synergize with other potesial sector in order to produce a multiplier effect on the communities increased revenue and the acceleration of economic development and multiply again the sectors that potential still to be developed so that the future is expected to be a potentially valuable sector. Keywords: The economic structural transformastion, Specialization, Competitive advantage, Location quotient (LQ). Abstrak: Tujuan utama dari penelitian ini adalah (1) untuk mengetahui transformasi struktural ekonomi di Aceh; dan (2) untuk menganalisis sektor-sektor ekonomi yang potensial untuk dikembangkan di Aceh. Metode penelitian ini menggunakan pendekatan Analisis Shift Share Klasik, Analisis Shift Share Esteban-Marquillas dan Location Quotient (LQ). Hasil analisis menunjukkan bahwa perekonomian Aceh mulai terjadi pergeseran dari sektor primer menuju ke sektor tertier dan sektor sekunder pada tahun 2008-2012 sedangkan tahun 2000-2004 dan tahun 2004-2008 belum terjadinya transformasi. Terjadinya transformasi struktural ekonomi pada tahun analisis 2008-2012 karena kontribusi dari sektor primer yang semakin menurun dengan pertumbuhan yang relatif rendah sementara pada saat yang sama kontribusi sektor tertier semakin meningkat dengan pertumbuhan yang relatif tinggi yang diikuti dengan peningkatan dari sektor sekunder juga. Dan sektor pertanian, sektor pertambangan dan pengalian serta sektor jasa-jasa merupakan sektor unggulan (sektor basis) yang potensial untuk dikembangkan di Aceh. Diharapkan kepada pengambil kebijakan terutama di Provinsi Aceh, untuk dapat lebih memperhatikan dan mengembangkan sektor-sektor ekonomi yang ada di Aceh dapat dilakukan dengan mengeluarkan kebijakan-kebijakan yang pro potensial untuk pengembangan sektor ekonomi dan juga merumuskan kebijakan untuk mulai mengembangkan sektor-sektor unggulan dengan memfokuskan pada sektor-sektor yang memiliki keunggulan serta mensinergikan dengan sektor potesial lainnya agar menghasilkan multiplier effect terhadap peningkatan pendapatan masyarakan dan percepatan pembangunan ekonomi serta mengali lagi sektor-sektor yang masih belum potensial untuk dikembangkan sehingga kedepannya diharapkan akan menjadi sektor yang bernilai potensial. Kata Kunci: Transformasi struktur ekonomi, Spesialisasi, Keunggulan kompetitif, Location quotient (LQ).